Jacques Rancière : key concepts - Deranty, Jean-Philippe (Key concepts (Acumen Publishing), 2014)
This introduction to Rancière's work covers the full range of his contribution to contemporary thought, presenting the key concepts he has developed in his writings over the past 40 years.